Mixing Design for ATIG Morphology and Microstructure Study of 316L Stainless Steel - Touileb, K.; Hedhibi, A.; Djoudjou, R.; Ouis, A.; Bouazizi, M. L. (Engineering, Technology & Applied Science Research, 2019)
This work is a study of the effects of oxides combination on the morphology of 316L stainless steel welds. A series of thirteen weld lines were carried out using thirteen different oxides. Based on the depth and ratio D/W results, three candidate oxides were selected: Ti2O, Mn2O3, and SiO2. Mixing method available in Minitab 17 software is the most appropriate method to find the optimal combinations to get the best depth and D/W ratio. According to simplex lattice degree four, nineteen combinations of these oxides were prepared. The results show that the optimal composition of flux was: 66%SiO2-34% Mn2O3. The depth and D/W ratio increased to 8.85mm and 0.98 respectively for optimal ATIG, whereas for the conventional TIG welding, the depth and the ratio D/W didn’t exceed 1.65mm and 0.17 respectively. For TIG weld joint the hardness is about 47 HRA and it increases to 77 HRA for the optimal ATIG weld joint. The absorbed energies in Charpy impact test are 146 and 138kJ in the weld zone and in the heat affected zone respectively for the TIG welding and they dropped to 111 and 74kJ for the optimal ATIG welding. The fracture surface examined by scanning electron microscope (SEM) shows a ductile fracture for TIG weld with small dimples but ductile-brittle fracture for ATIG weld. Energy dispersive spectroscopy (EDS/SEM) analysis shows the formation of FeS2 and SiO2 in the weld zone causing low absorbed energy for ATIG weld.